Determination Of Factory Location PT. Kelola Lingkungan Kita Using Factor Rating - Rio Ramadhan; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Diana Fajarwati (Penerbit Kemala Indonesia, 2020)
The initial stage before establishing a B3 medical waste processing plant PT. Kelola Lingkungan Kita (PT. KLK), it’s one of determines the right location. By choosing the right location can make transportation faster and more affordable to several hospitals in regional 1 or the island of Java and can improve company operations more effectively. This company using methods Location Factor Rating (LFR) by selecting the areas of Jakarta, Tangerang, Bekasi and Indramayu, Thus the calculation is done and the company location is obtained with the highest value of 3.67, at Indramayu. Here, PT. KLK built its factory in Indramayu Regency Industrial Estate. In addition to the industrial area being safe from environmental disturbances, salaries of employees in the Indramayu area are still relatively low compared to other areas. This study aims to determine the exact location of the PT KLK factory. There are several other factors that have a significant influence on determining the location of the PT. KLK, namely Minimum Wage for Employees, Factory Surroundings and Fleet Mobilization. This will have an impact on the effectiveness of the company and can reduce the company's operating costs, so that PT. KLK establishes a factory in the Indramayu Industrial Estate with the aim of being able to avoid the risk of environmental disturbances around the factory such as Community Social Institutions which can hinder operational activities, complaints from local residents because they are afraid that the environment will be polluted by the presence of a waste processing company, the Minimum Wage for Employees in the Indramayu area is classified as cheaper than in Jakarta, Tangerang and Bekasi.